Investigating the Role of Teacher's Transformative Leadership in Fostering Technology Acceptance among Vocational High School Students - Tutik Susilowati; Nur Rahmi Akbarini; Yosep Tegar Prameswara (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
As education evolves, technology integration has become a key factor in enhancing learning quality. However, its effectiveness largely depends on teachers as the primary agents of implementation. This study examines the role of transformational leadership in influencing students' acceptance of technology in Vocational High Schools. The Technology Acceptance Model (TAM) is extended by incorporating Motivation for Use and Transformational Leadership as additional variables. Data were collected from 365 Vocational High School students in Surakarta and Karanganyar using a structured questionnaire. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to explore complex relationships. The results highlight the significant influence of teacher transformational leadership on students' perception of technology’s ease of use and usefulness. These findings emphasize the need for teacher training, technology integration in the curriculum, infrastructure support, and continuous evaluation to foster effective technology adoption in vocational education. Strengthening teachers’ transformational leadership can enhance students' motivation and willingness to embrace technology, ultimately improving learning outcomes in vocational schools.